2018
DOI: 10.1111/add.14216
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol industry involvement in policymaking: a systematic review

Abstract: AimsTo summarize the substantive findings of studies of alcohol industry involvement in national or supranational policymaking, and to produce a new synthesis of current evidence.MethodsThis study examined peer‐reviewed journal reports published in the English language between 1980 and 2016 of studies of alcohol industry involvement in policymaking. Included studies were required to provide information on data collection and analysis and to have sought explicitly to investigate interventions by alcohol industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
229
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(243 citation statements)
references
References 48 publications
(197 reference statements)
12
229
0
2
Order By: Relevance
“…A recent Australian analysis showed that delays by government in implementing alcohol warning labels were probably due in large part to lobbying by the alcohol industry . This is in keeping with systematic review evidence that a range of methods are used to influence alcohol policies, among which donations may serve to support long‐term relationship building with key political actors, and can be integrated with other methods of influence .…”
Section: Introductionmentioning
confidence: 99%
“…A recent Australian analysis showed that delays by government in implementing alcohol warning labels were probably due in large part to lobbying by the alcohol industry . This is in keeping with systematic review evidence that a range of methods are used to influence alcohol policies, among which donations may serve to support long‐term relationship building with key political actors, and can be integrated with other methods of influence .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence, governments are often reluctant to implement public health‐oriented policies. This is partly due to the formidable efforts of the alcohol industry , but also because many evidence‐based policy options are not widely supported by the general public . There is strong evidence that public opinion is a key contributor to public policy decisions , so understanding how public support for evidence‐based policy changes is important.…”
Section: Introductionmentioning
confidence: 99%
“…A high-risk approach targets a small number of high-risk drinkers, while a population-based strategy aims to reduce alcohol-related harms through interventions targeted at the whole population. Lobbyists representing the alcohol industry often argue that policies to reduce alcohol-related harm should be based exclusively on the former, high-risk approach (7). However, Krietman (8) and subsequent researchers (6,(9)(10)(11)(12) have demonstrated that the majority of alcoholrelated harms tend to occur among low and moderate-risk drinkers, simply because they are more numerous in the population than high-risk drinkers, who still have a higher individual risk of experiencing harms.…”
Section: Introductionmentioning
confidence: 99%